Prospective longitudinal study of dynamic depressive symptom trajectories and diabetes onset risk in older adults: a 10-year follow-up of the HRS and ELSA cohorts - Yu, Xiaolin; Zhang, Yuchen; Zhao, Xinran (Frontiers in Public Health, 2025)
BackgroundThe study aimed to examine the longitudinal relationship between depressive symptom trajectories and diabetes onset risk in older adults, with particular attention to sex-specific variations.MethodsData were drawn from the Health and Retirement Study (HRS) and the English Longitudinal Study of Ageing (ELSA). Depressive symptoms were measured using CESD-8, and five trajectories were identified: consistently low, decreasing, fluctuating, increasing, and consistently high. Symptoms were further divided into somatic and cognitive-affective domains. Cox proportional hazards models were applied to estimate diabetes onset risk, controlling for demographics, health behaviors, and comorbidities. Analyses stratified by sex were conducted to assess differential effects.ResultsA total of 8,741 participants aged 50 years and older from both cohorts were included. During 10 years of follow-up, increasing (HR = 1.746, 95% CI: 1.195–2.551, p = 0.004) and consistently high (HR = 1.376, 95% CI: 1.042–1.818, p = 0.024) depressive trajectories were associated with greater diabetes risk compared with the consistently low group. No significant associations were detected for decreasing or fluctuating trajectories. Stronger associations were observed in women, including increasing (HR = 2.007, 95% CI: 1.290–3.121, p = 0.002) and consistently high (HR = 1.586, 95% CI: 1.161–2.167, p = 0.004) patterns. Similar associations were present across both cognitive-affective and somatic domains.ConclusionPersistent or worsening depressive symptoms serve as significant predictors of diabetes onset risk, particularly among women. Both cognitive-affective and somatic domains contribute independently, emphasizing the importance of dynamic mental health surveillance in diabetes prevention.